Courses for Kids
Free study material
Offline Centres
Store Icon

Convert given statement to equation form:
Mohan is $ 3 $ years older than Sohan. The sum of their ages is $ 43 $ years.

Last updated date: 13th Jun 2024
Total views: 403.2k
Views today: 5.03k
403.2k+ views
Hint: In this problem we first let age of Sohan as ‘x’ because Mohan is older than Sohan by $ 3 $ years. So, after letting age of Sohan as ‘x’ we can use it to get the age of Mohan and then using the given condition of their sum ages to calculate the value of ‘x’.

Complete step-by-step answer:
Mohan is older than Sohan by $ 3 $ years.
So, let the age of Sohan be ‘x’
Then age of Mohan is will be = $ \left( {x + 3} \right) $ years
Also, it is given that in question the sum of their ages is $ 43 $ years
Therefore, we have
  x + x + 3 = 43 \\
   \Rightarrow 2x = 43 - 3 \\
   \Rightarrow 2x = 40 \\
   \Rightarrow x = \dfrac{{40}}{2} \\
   \Rightarrow x = 20 \\
Hence, from above we see that the age of Sohan is $ 20 $ years and the age of Mohan is $ 23 $ years.

Note: While doing this type of age’s problems in which age of one person depends upon the age of another person. Age of that person should be taken ‘x’ whose age is not depending on the other person’s age.